POSTINGAN CYBERBULLYING RUHUT SITOMPUL TERHADAP BACAPRES ANIES BASWEDAN: ANALISIS WACANA KRITIS - Somantri, Wendra Riyadi; Nurhadi, Jatmika (Universitas Muhammadiyah Surabaya, 2024)
Social media such as X is currently a common consumption for people to obtain and disseminate certain information. However, there are negative sides of social media such as hate speech and bullying which is commonly referred to as Cyberbullying. Based on the problem, the purpose of this research is to show the discourse of Cyberbullying in X posts from Ruhut Sitompul's account that are bullying presidential candidate Anies Baswedan. The method used in this research is Critical Discourse Analysis with data taken in the form of images and written discourse which are then analyzed using Teun A. Van Dijk's three dimensions. The results of this study will show how cyberbullying carried out by Ruhut Sitompul and netizen comments can be explained through Teun A. Van Dijk's three-dimensional Critical Discourse Analysis, namely: (1) Macrostructure Analysis (Thematic); (2) Superstructure Analysis (Schematic); and (3) Microstructure Analysis. Based on the findings, the conclusion that will be generated is that the discourse of Cyberbullying can be known the intent and purpose of the utterance through the discourse of Teun A. Van Dijk's Critical Discourse Analysis model.